Pengembangan Media Pembelajaran Interaktif Berbasis Google Sites Pada Materi Pancasila Bagi Peserta Didik Sekolah Dasar (Universitas Negeri Padang, 2023)
This study aims to create interactive learning media, named Pancasila-Ku, using Google Sites to enhance Pancasila education for fourth-grade students at SDN Jatinegara Kaum 03. The media design is grounded in addressing diverse learning styles among children. The Research and Development (R&D) approach, following the Hannafin and Peck model, guides the research process. The media's validity is evaluated through expert validation, with media experts giving a score of 92.2%, language experts 71.1%, and subject matter experts 90%. Practical testing involving fourth-grade students indicates positive outcomes, scoring 90.6% in the one-to-one stage, 90.8% in the small group stage, and 91% in the field test stage. The findings affirm the suitability of Pancasila-Ku for Pancasila education among fourth-grade students, emphasizing its role as the foundation of the state. Consequently, the study's objectives are achieved, and the developed interactive learning media is endorsed for use in elementary schools.